Amyotrophic Lateral Sclerosis: New Perpectives and Update - Orsini, Marco (Neurol Int, 2015)
Amyotrophic lateral sclerosis (ALS), Charcot’s disease or Lou Gehrig’s disease, is a term used to cover the spetrum of syndromes caracterized by progressive degeneration of motor neurons, a paralytic disorder caused by motor neuron degeneration. Currently, there are approximately 25,000 patients with ALS in the USA, with an average age of onset of 55 years. The incidence and prevalence of ALS are 1-2 and 4-6 per 100,000 each year, respectively, with a lifetime ALS risk of 1/600 to 1/1000. It causes progressive and cumulative physical disabilities, and leads to eventual death due to respiratory muscle failure. ALS is diverse in its presentation, course, and progression. We do not yet fully understand the causes of the disease, nor the mechanisms for its progression; thus, we lack effective means for treating this disease. In this chapter, we will discuss the diagnosis, treatment, and how to cope with impaired function and end of life based on of our experience, guidelines, and clinical trials. Nowadays ALS seems to be a more complex disease than it did two decades – or even one decade – ago, but new insights have been plentiful. Clinical trials should be seen more as experiments on pathogenic mechanisms. A medication or combination of medications that targets more than one pathogenic pathway may slow disease progression in an additive or synergistic fashion.